Jejunal Intussusception Due to Heterotopic Pancreas: A Case Report - Daniel, Nsikak E (Cureus, 2021)
Intussusception in adults is rare. Even more unusual is jejunal intussusception secondary to a heterotopic pancreas. The presence of pancreatic tissue in an ectopic location and lacking contiguity with the main pancreatic gland is defined as pancreatic heterotopia. It is very rarely symptomatic and usually diagnosed incidentally during surgical intervention for other conditions. We report the case of a 78-year-old lady who presented with a history of constipation, abdominal pain, and vomiting. A CT scan revealed features of a proximal jejunojejunal intussusception secondary to a small soft tissue density lead point. After laparotomy and segmental jejunal resection, histopathology confirmed the diagnosis of ectopic pancreatic tissue as the lead point. Although uncommon, heterotopic pancreatic tissue should be included in the differential diagnosis for proximal small bowel intussusception.